2023
DOI: 10.1093/jsxmed/qdad054
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep disorders, quality, and duration and sexual dysfunction: a systematic review and meta-analysis

Abstract: Background The associations between sexual dysfunction (SD) and sleep disorders, sleep quality, and sleep duration remain unclear. Aim To assess the relationship between sleep and SD through a literature review and meta-analysis. Methods The PubMed, Scopus, Embase, Ovid MEDLINE, and Cochrane Library databases were systematically searched from inception to Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“… 42 Additionally, heightened levels of reactive oxygen species promote arterial stiffness, contributing to the progression of atherosclerosis and vascular endothelial dysfunction, ultimately leading to reduced blood flow to the penis. 43 Moreover, it is significant to acknowledge that patients with CKD commonly experience lowered erythropoietin levels and exhibit heightened levels of prolactin, which ultimately leads to an increased incidence of anemia and decreased levels of hemoglobin. Previous studies have demonstrated that these factors can influence erectile function by impacting hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Additionally, heightened levels of reactive oxygen species promote arterial stiffness, contributing to the progression of atherosclerosis and vascular endothelial dysfunction, ultimately leading to reduced blood flow to the penis. 43 Moreover, it is significant to acknowledge that patients with CKD commonly experience lowered erythropoietin levels and exhibit heightened levels of prolactin, which ultimately leads to an increased incidence of anemia and decreased levels of hemoglobin. Previous studies have demonstrated that these factors can influence erectile function by impacting hormone secretion.…”
Section: Discussionmentioning
confidence: 99%